“The Harsh Reality of Being a Woman”: First Bra Experiences - Brodie, Ian (Ethnologies, 2007)
AbtractThe first bra purchase, which implies the first bra wearing or at least the first bra specifically purchased for the young woman, introduces two phases beyond the demarcation of girl as woman: a lifetime of wearing bras and a lifetime of shopping for bras. In an effort to explore some of the consequences of using the term “rites of passage” in contemporary contexts, this article sets out to identify the elements common to the “rite” of the first bra purchase. It is an activity more or less inevitable in North American women’s culture; it is a commercial transaction, and thus can be affected by socioeconomic class status; and it is inherently associated with the transformations of puberty, both physiological and social (in van Gennep’s sense). Finally, although it is distinct from adolescent sexuality, it is nevertheless virtually inextricable therefrom and thus a gendered activity, one from which the male fieldworker is excluded for reasons that extend far beyond mere impropriety.